Global Value Chain Configuration: A Review and Research Agenda. Issue 2 (April 2017) - Hernández, Virginia; Pedersen, Torben
This paper reviews the literature on global value chain configuration, providing an overview of this topic. Specifically, we review the literature focusing on the concept of the global value chain and its activities, the decisions involved in its configuration, such as location, the governance modes chosen and the different ways of coordinating them. We also examine the outcomes of a global value chain configuration in terms of performance and upgrading. Our aim is to review the state of the art of these issues, identify research gaps and suggest new lines for future research that would advance our understanding of how firms are implementing new ways of organizing and managing activities on a global scale.